2015
DOI: 10.1007/s40801-015-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Economic Burden in Patients Treated for Acromegaly in the USA

Abstract: BackgroundAcromegaly is a rare, debilitating condition for which data on the associated treatment patterns and economic burden are limited.ObjectiveOur objective was to examine patient characteristics, treatment patterns, and healthcare resource utilization (HRU)/costs for individuals with acromegaly treated with surgical and/or medical therapy in the USA.MethodsUsing a large US claims database, adults with new episodes of acromegaly between 1 July 2007 and 31 December 2010 were identified (the first observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Both groups utilized the physician's office most often, followed by outpatient facilities, laboratory services, and other sites of care, even though the frequency of use was quite different between groups for most venues. Finding that healthcare service use in general was significantly greater (in many cases, several-times greater) for patients with acromegaly, this analysis corroborates and builds upon previous estimates of the economic burden of acromegaly [7,16,19,29].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Both groups utilized the physician's office most often, followed by outpatient facilities, laboratory services, and other sites of care, even though the frequency of use was quite different between groups for most venues. Finding that healthcare service use in general was significantly greater (in many cases, several-times greater) for patients with acromegaly, this analysis corroborates and builds upon previous estimates of the economic burden of acromegaly [7,16,19,29].…”
Section: Discussionsupporting
confidence: 84%
“…Using administrative coding for patient identification, this methodology permitted exclusion of patients with other conditions, such as Cushing's disease, without relying on patient recall or subjective measures. By contrast, previous studies [7,16,18,29] did not exclude patients with Cushing's disease or other pituitary disorders. Though not the primary focus, this study also explored the impact of concurrent hypopituitarism.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
See 1 more Smart Citation
“…Chuang and colleagues 8 published the results of claims database analysis from 2007 to 2010 of 397 patients with acromegaly and stratified them into groups receiving surgical resection with/without medical therapy or medical therapy only. Their study demonstrated that patients who had received surgery had 69% higher mean direct healthcare costs compared with those in the medical therapy only.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of acromegaly that have been published utilize federal or commercial databases to analyze prevalence, treatment patterns, and adherence. [6][7][8][9][10] However, data on the impact of acromegaly on employees' health costs (direct and indirect) are limited. Furthermore, even less J o u r n a l P r e -p r o o f 6 | P a g e Running Title: Costs in Patients with Acromegaly information is available on the burden of acromegaly from an employer's perspective, including health benefit costs and worker productivity.…”
Section: Introductionmentioning
confidence: 99%